Safety and reliability of dobutamine stress echocardiography in pediatric and young adult patients with coronary arteries abnormalities. (4th February 2022) - Bianco, F; Bucciarelli, V; Colaneri, M; Surace, FC; Berton, E; Baldoni, M; Arcieri, L; Baldinelli, A; Gallina, S; Pozzi, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study was conducted with the support of Regione Marche, Italy Background: Risk stratification in coronary arteries abnormalities (CAA), both anomalous aortic origin of a coronary artery (AAOCA) and myocardial bridges (MBs), is still challenging. A reliable method to detect myocardial ischemia is missing in these anomalies. We studied the safety and feasibility of dobutamine stress echocardiography (DSE), compared with exercise stress echocardiography (ESE), in pediatric and young adult patients with CAA. Methods: In 2019-21, N = 27 CAA [median age 16 years (Q1–Q3: 11, 22)] (n= 23 AAOCA, n = 4 MBs) were assessed. ESE was performed 1-2 days before the DSE examination, double-blinded for examiners and patients. Hemodynamic response and major (cardiac arrest, myocardial infarction, ventricular arrhythmia) and minor [hypertension (≥ 200/120 mmHg), paradoxical bradycardia, chest pain, nausea/vomiting, skin rash, anxiety, dizziness, dyspnea] events were recorded. Differences between rest/stress and DSE/ESE for wall motion abnormalities (WMA) and global longitudinal strain (GLS) were evaluated. Inter-observer agreement was also tested using the kappa (k) coefficient. Results: Heart rate and blood pressure increased significantly from baseline (p < 0.001) in both DSE and ESE exams. Only DSE tests reached a heart rate ≥ 150 bpm (p < 0.001), while younger patients barely reached the heart rate target and frequently showed less compliance to the test. No patient had major events, while 5 (18.5%) had minor events, the majority during DSE. Inducible WMA were observed only at DSE examinations. Inter-observer agreement for WMA and GLS changes was good for both examinations (95%, k = 0.85, p < 0.001). Conclusions: DSE is feasible in pediatric and young adult patients with AAOCA and MBs to assess inducible WMA and GLS rest/stress changes. It can be performed safely with a low incidence of major/minor events, with a better performance when compared to ESE. DSE is potentially a valuable test for detecting myocardial ischemia and probably helpful in managing CAA patients.